In Vitro Biocompatibility of Multiwalled Carbon Nanotubes with Sensory Neurons. Issue 5 (8th November 2012) - Gladwin, Karen M.; Whitby, Raymond L. D.; Mikhalovsky, Sergey V.; Tomlins, Paul; Adu, Jimi
Abstract Multiwalled carbon nanotubes (MWCNTs) possess unique properties rendering them a potentially useful biomaterial for neurobiological applications such as providing nanoscale contact‐guidance cues for directing axon growth within peripheral nerve repair scaffolds. The in vitro biocompatibility of MWCNTs with postnatal mouse spinal sensory neurons was assessed for this application. Cell culture medium conditioned with MWCNTs was not significantly toxic to dissociated cultures of postnatal mouse dorsal root ganglia (DRG) neurons. However, exposure of DRG neurons to MWCNTs dispersed in culture medium resulted in a time‐ and dose‐dependent reduction in neuronal viability. At 250 μg mL−1, dispersed MWCNTs caused significant neuronal death and unusual neurite morphologies illustrated by immunofluorescent labelling of the cytoskeletal protein beta (III) tubulin, however, at a dose of 5 μg mL−1 MWCNTs were nontoxic over a 14‐day period. DRG neurons grown on fabricated MWCNT substrates produced neurite outgrowths with abnormal morphologies that were significantly inferior in length to neurons grown on the control substrate laminin. This evidence demonstrates that to be utilized as a biomaterial in tissue scaffolds for nerve repair, MWCNTs will require robust surface modification to enhance biocompatibility and growth promoting properties.